Jahresprogramm Kunsthalle Basel 1984. - Kunsthalle, Basel (Basel : Kunsthalle Basel, 1985)
Baer, Peter ; Baselitz, Georg ; Clemente, Francesco ; Kruger, Barbara ; Holzer, Jenny ; Kaempf, Max ; General Idea ; Wall, Jeff ; etc.
Duits
boek